A study of empowering entrepreneurship for employees in the shipyard industry - Fifi Hariani; Hamidah Hamidah; Mahmuddin Yasin (Trigin Publisher, 2022)
This research focuses on how empowerment conditions in the shipbuilding industry can affect employee entrepreneurship. This research is qualitative research conducted on case studies of shipyard companies in Batam, Indonesia. Interestingly, this research was conducted on employees with special skills who were affected by Termination of Employment. So that in this study those who have been laid off but have special skills must be able to have entrepreneurship. The results of this study indicate that there are different perspectives from employees affected by the termination of employment, with the company's perspective. The results show that there are 3 important factors that can increase entrepreneurship, namely creativity and innovation, risk, commitment, and loyalty. Meanwhile, there was 1 new factor found, namely the mindset to be able to increase employee entrepreneurship.